Da escrita ou de um longo caminho para um possível final bem sucedido - Pinto, Maria da Graça L. Castro (Linguarum Arena, 2018)
A escrita ao longo da vida; aquisição/aprendizagem da escrita; a escritacomposição; políticas educativas (académica e baseada no jogo); a densidade de ideias e a complexidade gramatical/sintáctica na escrita. This text attempts to provide as brief and as adequate a look as possible at writing over an average lifespan so that reasonable levels of idea density and grammatical complexity may be observed in texts written in later life as well as during adulthood. As the quality of young adults’ written production may be an indicator of what will happen later in life, it is important to do the best we can in terms of emergent literacy in early childhood and create good writing habits in the population in general. Children should be familiar with writing as composition and not only as a mere mechanism. Hence, academic and play-based programmes should be combined, and the child as a whole, as well as different cognitive skills, and emotional and social systems taken into account. Looking at writing in this way, children may get the appropriate bases on which to be successful at school, and later on, as adults, they may feel like proficient agents of writing as they are of other skills they are used to performing.